INFLUENCE OF SOIL PARAMETERS ON THE VALUE OF THE MODULUS OF THE VERTICAL TRACK ELASTICITY - Danovych, V. D.; Rybkin, V. V.; Patlasov, O. M.; Bondarenko, I. O. (Science and Transport Progress, 2003)
The necessity of updating of values of the vertical module of a track elasticity is proved, by taking info account of a sort of the subarade soil its state both thickness of a ballast layer and its state. The numerical rating of parameters influencing the module of the track elasticity is given.